Intelligent sustained‐release microgel for reduced permeability of fluid channels: Synthesis and properties. Issue 25 (11th February 2021) - Yu, Qin; Song, Kaoping; Cai, Jiangchao; Li, Jihang; Gao, Tenglong
Abstract: Polymer microspheres as fluid diverting agents have been applied for profile control in deep reservoirs. However, its reservoir adaptability strictly requires the matching between the particle size and the pore radius, which are hard to realize due to uncertainty of pore radius caused by long‐term water flooding. That behavior has severely reduced their plugging performance to the large channel. The objective of this study was to prepare a kind of intelligent sustained‐release microgel to solve the problem, which could slowly release of sodium silicate during migration, form the larger aggregates and plug high permeability reaching deep reservoir. We developed a novel blocking agent, which is an amphoteric microgel (OICMS) synthesized by light‐initiated polymerization followed by the adsorption of a sodium silicate solution. The microgel properties, including the adsorption and release properties of a sodium silicate solution, and its influencing factors were investigated. The results showed that the OICMS had larger adsorption and release ratio of sodium silicate than conventional polymer microspheres, influenced by the ionic degree, molecular weight, amount of pore‐forming agent, and cross‐linking density. Abstract : We prepared a kind of intelligent sustained‐release microgel, which could selectively enter the target reservoir, slowly release sodium silicate, form the larger aggregates by interacting with divalent ions and plug high permeability in deep reservoirs. Thus, the microgel with its intelligent sustained‐release capabilities makes it attractive for profile control applications..